Effects of variable deoxygenation on trace element bioaccumulation and resulting metabolome profiles in the blue mussel (Mytilus edulis). (July 2020) - Belivermiş, Murat; Swarzenski, Peter W.; Oberhänsli, François; Melvin, Steven D.; Metian, Marc
Abstract: The dissolved oxygen concentration of the world's oceans has systematically declined by 2% over the past 50 years, and there has been a notable commensurate expansion of the global oxygen minimum zones (OMZs). Such wide-scale ocean deoxygenation affects the distribution of biological communities, impacts the physiology of organisms that may affect their capacity to absorb and process contaminants. Therefore, the bioaccumulation efficiencies of three contrasting radionuclides, 110m Ag, 134 Cs and 65 Zn were investigated using controlled aquaria in the blue mussel Mytilus edulis under three contrasting dissolved oxygen regimes: normoxic; 7.14 mg L −1, reduced oxygen; 3.57 mg L −1 and hypoxic 1.78 mg L −1 conditions. Results indicated that hypoxic conditions diminished 110m Ag uptake in the mussel, whereas depuration rates were not affected. Similarly, hypoxia appeared to cause a decrease in the 65 Zn bioaccumulation rate, as evidenced by both weakened uptake and rapid elimination rates. Effects of hypoxia on the metabolome of mussels were also explored by untargeted Nuclear Magnetic Resonance (NMR) spectroscopic methods. The metabolic response was characterised by significantly greater abundance of several amino acids, amino sulfonic acids, dicarboxylic acids, carbohydrates and other metabolites in the lowest oxygen treatment, as compared to the higher oxygen treatments. Clearance rates significantly dropped in hypoxic conditions compared to normoxia. Results suggest that hypoxic conditions, and even partly moderate hypoxia, alter ventilation, an-aerobic, oxidative and osmoregulation metabolism of this mussel, which may further influence the trace element bioaccumulation capacity. Highlights: Hypoxic conditions diminished 110m Ag uptake in the mussel. Sixteen of 29 identified metabolites displayed higher abundance in hypoxia. Clearance rates significantly dropped in hypoxic conditions compared to normoxia. Hypoxia appeared to cause a decrease in 65 Zn bioaccumulation rate. An-aerobic, oxidative and osmoregulation metabolism of the mussel were altered by hypoxia.